Agroforestry system biodiversity of Arabica coffee cultivation in North Toraja District, South Sulawesi, Indonesia - ANDI LISNAWATI; ABUBAKAR M. LAHJIE; B.D.A.S. SIMARANGKIR; SYAHRIR YUSUF; YOSEP RUSLIM (Biodiversitas Journal of Biological Diversity, 2017)
Lisnawati A, Lahjie AM, Simarangkir BDAS, Yusuf S, Ruslim Y. 2017. Agroforestry system biodiversity of Arabica coffee cultivation in North Toraja District, South Sulawesi, Indonesia. Biodiversitas 18: 741-751. Sustainable coffee plantation emphasizes the concept that is able to provide services that can improve the quality of the environment and the ecosystem as a conservation efforts. Arabica coffee plants do not need full sunlight that they are planted according to agroforestry system which covers simple mix system to complex system such as forest. Shade tree has a very big role in sustainable coffee agro-ecosystem and become one of the conditions in the world's coffee certification. This study aimed to analyze the role of shade trees lamtoro types (Leucaena glauca), and calliandra (Calliandra calothyrsus) used by companies as an agroforestry systems on coffee cultivation in North Toraja located at an altitude between 1050-1250 m above sea level, this study was conducted from January to December 2016. Result of the study suggests that the shade trees lamtoro and calliandra influence the amount of sunlight intensity that reaches coffee plant. The shaded and unshaded coffee plants received different sunlight intensity of every minute with a coefficient of determination R2 = 0.98 for unshaded and R2 = 0.89 for under the shade of calliandra, with a diameter growth increased 7.8% year-1, increase growth (riap) diameter decreased 2% year-1. Cherry increased growth of 13.5% year-1 with an average weight of 3.81 g beans-1,while for the effect of lamtoro, the coefficient of determination is R2 = 0.98 for unshaded and R2 = 0.91 for under the shade. The percentage of light intensity outside and under the shade obtained from a 17 year coffee plant is on average of 58% for the types of tree of calliandra, while for lamtoro the average is of 72.5%, diameter growth of coffee tree in under shade lamtoro by 7.4% year-1 and increase of growth (riap) diameter decreased by 2.5% year-1, cherry growth increased by 13.3% year-1 with an average weight of 3.92 g beans-1. In addition to that, shading also affect the surrounding nutrient soil and maximum production of coffee is achieved at the age 17 years i.e. an average of 1.50 kg tree-1 for a shaded tree calliandra species and 1.35 kg tree-1 for lamtoro species.